Social Alliance and Employee Voluntary Activities: A Resource-Based Perspective - Liu, Gordon G.; Ko, Wai Wai (2011)
The corporate social responsibility literature devotes relatively little attention to the strategic role played by employee voluntary activities (EVAs) in social alliances. Using the resource-based perspective of the organization to frame the data collection and the analyses, this article investigates: (1) the role of EVAs in the development of corporate and non-profit organizations (NPOs) competitive assets and (2) the management approaches to how both parties can develop their own resources by combining them with the shared resources with the purpose of enhancing its competitive advantage in its own sector. The database is composed of 70 specifically designed interviews with managers of UK-based firms and NPOs. The analyses suggest, among other things, that the majority of corporate and non-profit managers find that EVAs generate substantial tangible and intangible benefits for their respective organisations, creating genuine synergies. We also find evidence of a general preference for the management approaches of such programmes in both types of organisation.
Keywords: Employee voluntary activities; Social alliances; Resource-based view; Corporate Social Responsibility